SYNTHESIS AND CHARACTERIZATION OF MAGNETIC METALLIC NANOWIRES AND THEIR NOVEL HYBRID NANOSTRUCTURES - IRSHAD, MUHAMMAD IMRAN (2016)
Metallic and magnetic nanowires (NWs) of cobalt, nickel, iron and copper exhibit great potential for various applications ranging from nano-interconnects, high density magnetic storage media, electrode material and as well as super-capacitors. However, the production of these good quality NWs is still not well understood as a result of lack of understanding on how their structural and magnetic properties depend on the parameters of the synthesis. In addition, the demand for multifunctional properties necessitates the development of novel pristine hybrid nanostructures based on these metallic NW s. Thus, the objective of this research work is to optimize the production of good quality metal NW s and to develop pristine hybrid structures of metal N W s and carbon nanotubes (CNTs). The electro-deposited NWs with average diameter of I 00 nm and high aspect ratio ranging from 300-400 were analyzed using characterization techniques for structural and magnetic properties.